Excellent via passivation and high open circuit voltage for large-area n-type MWT-PERT silicon solar cells. (September 2017) - Chen, Jia; Singh, Sukhvinder; Heide, Arvid van der; Duerinckx, Filip; Razzaq, Arsalan; Cornagliotti, Emanuele; Uruena, Angel; Tous, Loic; Russell, Richard; Govaerts, Jonathan; Gordon, Ivan; Dewallef, Stefan; et al.
Abstract: In this work, we improved the performance of the MWT-PERT solar cells focusing on increasing their Voc by combining the MWT concept with n-PERT technology. The impact of different post-laser treatments on the via surface morphology and the via passivation was investigated. KOH texturing can partially remove the laser damage in the via and reduce the via SRV to 1000 cm/s. With optimized post-laser treatment and via passivation, an average Voc of 685mV was achieved for our large-area n-type MWT-PERT cells. Front Ni/Cu plating and rear Ag and Al screen-printing were used for the metallisation, the compatibility of this hybrid metallisation scheme was studied. Using industrial solder-through interconnection technology, the cell was integrated in a laminate reaching a one-cell module efficiency at 20%. The reliability of the one-cell modules was preliminarily investigated in an extended reliability test.